(untitled) (Global Journal of Medical Research, 2020)
The objectives of this study were to test the effect of Nd: YAG Laser welding parameters (WP, PE, Ton and WS) on the HAZ of C.P Ti and T-6Al-7Nb alloys. The chosen Nd: YAG Laser welding parameters were three levels and CCD was selected to design the experiments. A 2nd regression equation relating to outputs and Nd: YAG Laser welding parameters was developed by using RSM. The result conducted that all the main effects of input parameters, i.e., WP, PE, Ton, and WS were found to be highly significant in affecting the HAZ.